Advances in the Diagnostic Evolution and Treatment of Atypical Lobular Endocervical Glandular Hyperplasia - Guoqiu Dong; Liying Yu; Xiaoqin Zhang; Lifeng Xu (Discovery Medicine, 2026)
Atypical lobular endocervical glandular hyperplasia (ALEGH) is a cervical precancerous lesion that develops independently of high-risk human papillomavirus (HPV) infection. It is regarded as a key intermediate stage in the progression from lobular endocervical glandular hyperplasia to gastric-type endocervical adenocarcinoma (G-EAC). Because these lesions are often located in the upper endocervical canal or deep cervical stroma, and their cytological and histological atypia may be subtle, ALEGH is prone to being missed or misdiagnosed in clinical practice. Accurate identification of ALEGH and assessment of its malignant potential are central to improving clinical management. In recent years, advances in multimodal imaging, artificial intelligence (AI)-assisted image analysis, preoperative targeted biopsy, and molecular pathology have provided new evidence for improving preoperative detection and risk stratification. In this review, we summarize the current evidence regarding the imaging diagnosis, preoperative pathological confirmation, molecular mechanisms, and stratified clinical management of ALEGH, with the aim of providing practical reference for early recognition, malignant risk assessment, fertility-preserving decision-making, and surgical management of high-risk ALEGH cases.